Investigating the In Vitro Osteogenic Properties of the Inclusion Nanocarrier of Icariin with Beta-Cyclodextrin-Alginate - Somang Choi; Yeong Seok Lee; Han-Saem Jo; Woong Kyo Jeong; Hak-Jun Kim; Mi Hyun Song; Kyeongsoon Park; Sung Eun Kim (Applied Sciences, 2020)
In this study, we created an inclusion nanocarrier of icariin (ICA) and β-cyclodextrin-alginate conjugate (ICA/β-CD-ALG) and determined its in vitro osteogenic ability on MC3T3-E1 cells. The morphological shape of the prepared β-CD-ALG with or without ICA was nano-sized and round. The use of β-CD-ALG achieved a sustained ICA release for up to 7 days. In vitro studies found that ICA/β-CD-ALG had a greater potential in osteogenesis on MC3T3-E1 cells compared to β-CD-ALG by exhibiting both higher alkaline phosphatase levels and the amount of calcium deposits. Moreover, ICA/β-CD-ALG greatly increased the levels of osteogenesis markers including osteocalcin (OCN) and osteopontin (OPN). Our results suggest that ICA/β-CD-ALG plays a significant role in cellular osteogenic activity.